Influence of chemical and mechanical polishing on water sorption of acrylic resins polymerized by water bath and microwave irradiation - Morgana Nicoleti Gabrioti; Lais Regiane da Silva Concilio; Margarete Cristiane Ribeiro-Dasilva; Jeremiah Edillor Juson; Célia Marisa Rizzatti Barbosa (Universidade Estadual de Campinas, 2016)
Previous studies have investigated the possible influences to different types of polymerization and polishing procedures in some properties of acrylic resins. Water sorption is an important property, which may be induced by these factors. The aim of this work was to evaluate water sorption in acrylic resin processed in microwave energy or water bath, after chemical and mechanical polishing. Forty heatpolymerized acrylic resin (Vipi-Cril, Dental VIPI Ltd, Pirassununga, São Paulo, Brazil) specimens were made according to ADA Specification No.12 for Denture Base Polymers and divided into 4 groups: Groups I and II were processed in microwave energy (500 W for 3 minutes); Groups III and IV, in water bath (73ºC ± 1ºC for 9 hours). Groups I and III were polished chemically; Groups II and IV were polished mecahnically. The specimens were submitted to water sorption test. The water sorption values (mg/cm2 ) were calculated and submitted to ANOVA and Tukey´s test (5% significance level). The obtained results were: Group I: 0.000953, Group II: 0.001069, Group III: 0.000958 and Group IV: 0.001491. No statistical difference were found among the groups (p>.05). Polymerization by microwave energy or water bath associated with chemical or mechanical polishing did not influence the water sorption of the heat polymerized acrylic resin evaluated.